2020
DOI: 10.1186/s12866-020-01999-x
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota characteristics in mice with antibiotic-associated diarrhea

Abstract: Background Antibiotic-associated diarrhea (AAD), defined as diarrhea that occurs in association with the administration of antibiotics and without another clear etiology, is one of the most common adverse drug events of antibiotics therapy. We established a diarrhea model induced by gentamycin and cefradine to investigate the microbiota characteristics in the intestinal lumen of mice with AAD and provide insights into noteworthy bacteria related to gentamicin and cefradine-associated diarrhea. Results The nu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 38 publications
0
43
0
Order By: Relevance
“…Clostridium is a Gram-positive anaerobe that produces spores and is the most common pathogen in antibiotic-associated diarrhea [ 59 ]. Shao et al [ 60 ] found that the number of Clostridium in the intestinal tract of antibiotic-associated diarrhea model mice established by gentamicin and cefradine was significantly increased. Lincomycin has also been used as an inducer for antibiotic-associated diarrhea [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clostridium is a Gram-positive anaerobe that produces spores and is the most common pathogen in antibiotic-associated diarrhea [ 59 ]. Shao et al [ 60 ] found that the number of Clostridium in the intestinal tract of antibiotic-associated diarrhea model mice established by gentamicin and cefradine was significantly increased. Lincomycin has also been used as an inducer for antibiotic-associated diarrhea [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Relevant sequences were aligned with the software Muscle [ 44 ] (version 3.8.31) and clustering trees were constructed using the FastTree [ 45 ] (version 2.1) and UPGMA (Unweighted Pair Group Method with Arithmetic Mean) software. Multivariate statistical techniques including PCoA (principal coordinates analysis) [ 46 ] and NMDS (non-metric multi-dimensional scaling) [ 47 ] of Bray-Curtis distances were calculated using the Vegan package (version 2.5.3) and plotted using ggplot2 package (version 2.2.1).…”
Section: Methodsmentioning
confidence: 99%
“…Previously, numerous studies were performed on pathogenic bacteria, parasite, and virus to reveal the cause of ruminant diarrhea ( Gallardo et al, 2020 ; He et al, 2020 ). Recent studies on gut microbiota of goat, yak, and mice have provided evidence that gut microbial dysbiosis may be one of the reasons of diarrhea ( Han et al, 2017 ; Shao et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Metagenomic analysis based on high-throughput sequencing technology is an efficient tool for characterizing gut microbial composition and diversity differences after suffering certain diseases and has made possible in systematically investigating the relationship between host diseases and gut microbiota ( Han et al, 2017 ; Shao et al, 2020 ). Moreover, in-depth comparison and analysis of obtained gut microbial information contributed to further understand the mechanisms causing ill health and develop the strategies to minimize the collateral damage ( Han et al, 2017 ; Shao et al, 2020 ). Giraffe ( Giraffa camelopardalis ) mainly inhabiting the African continent is the tallest terrestrial ruminant in the world and displays a complicated gastrointestinal microbial ecosystem ( Brown et al, 2007 ; AlZahal et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%